PERKEMBANGAN KOGNITIF TOKOH EMMANUEL DALAM KINDERROMAN DIE GESCHICHTEN VON DER GESCHICHTE VOM PINGUIN KARYA CHRISTINE NÖSTLINGER - Khairunnisa, Jasmine; Nurdiawan, Indra (Universitas Ahmad Dahlan, 2023)
This study aims to examine the level of cognitive development and elaborate the factors that influence the level of cognitive development of the figure of Emanuel in the romance Die Geschichten von der Geschichte vom Pinguin by Christine Nöstlinger using Vygotsky's theory of the level of cognitive development. This research is a type of qualitative descriptive research that uses a literary psychology approach. Meanwhile, the instrument in this study is the researcher himself (human instruman). Data collection techniques are carried out by the literature study method and the validity of the data is carried out by validity tests and reliability tests. The results showed that there were two stages of cognitive development experienced by Emanuel's character in Kinderroman Die Geschichten von der Geschichte vom Pinguin, namely the actual developmental stage and the potential developmental stage. The actual stage of development is shown by the way Emanuel's character solves his problems independently, namely being able to deal with penguins independently and find solutions to each problem he faces. The potential stage of development is shown in the way Emanuel's character solves problems with the guidance of adults, namely the characters Emma and Malwine. Meanwhile, the factors that influence the level of cognitive development of Emanuel's character found in the romance Die Geschichten von der Geschichte vom Pinguin are family atmosphere factors, family economic conditions factors and social environment factors.